Graduate Employability Programmes in Malaysian Higher Learning Institutions. - Abdul Rahman, Shukran; CihatDrTurki, CihatDrTurki (Cambridge Scholars Publishing, 2019)
Higher Education sector has been expected to produce knowledgeable and competent graduates, and Higher Learning Institutions are expected to be significant players of workforce development institutions. The presence of competent workforce is crucial for the advancement of a country’s social growth and economic prosperity. This paper addresses an intervention introduced by Higher Education authority in Malaysia to address the emerging unemployment issues in the country. A number of Graduate Employability Programmes (GEP) have been organised by Higher Learning Institutions (HLI) with the aim of enhancing the level of employability among their graduates. GEP is an important effort that involves efforts of the Government and private sectors to enhance the quality of HLI graduates. The effort is driven, among other factors, by the expectation of employers who prefer graduates who have high level of readiness to be in the workforce. The Ministry of Higher Education has organised, or funded, a number of GEPs. The purpose of this paper to present the background concept of GEP, and the framework of GEP.